Clearing the smoke : assessing the science base for tobacco harm reduction - Stratton, Kathleen R. (Institute of Medicine, National Academy Press, 2001)
The National Academy Press, based in Washington, D.C. presents the full text of the book entitled "Clearing the Smoke: Assessing the Science Base for Tobacco Harm Reduction," edited by Kathleen Stratton, Padma Shetty, Robert Wallace, and Stuart Bondurant. The book was originally published in 2001. The book discusses the evaluation of products that claim to reduce the need to smoke while allowing nicotine consumption.